2020
DOI: 10.3389/fpsyt.2020.00572
|View full text |Cite
|
Sign up to set email alerts
|

Highly Recurrent Copy Number Variations in GABRB2 Associated With Schizophrenia and Premenstrual Dysphoric Disorder

Abstract: Objective Although single-nucleotide polymorphisms in GABRB2 , the gene encoding for GABA A receptors β2 subunit, have been associated with schizophrenia (SCZ), it is unknown whether there is any association of copy number variations (CNVs) in this gene with either SCZ or premenstrual dysphoric disorder (PMDD). Methods In this study, the occurrences of the recurrent CNVs esv2730987 in Intron 6 and nsv1177513 in Exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…A wide range of schizophrenia-like phenotypes displayed by the GABRB2 -knockout mice, and the reversal of these phenotypic alterations by antipsychotic drug further underline the pivotal role of GABRB2 in the development of schizophrenia [ 98 ]. As well, the association between GABRB2 and schizophrenia has been validated by multiple genetic studies on different ethnic populations [ 99 101 ], and SNPs, haplotypes and CNVs in the 3551-bp segment are found to be associated with schizophrenia taking a candidate gene approach [ 102 , 103 ]. However, genome-wide association studies report no significant association between any of the SNPs in this 3551-bp segment and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of schizophrenia-like phenotypes displayed by the GABRB2 -knockout mice, and the reversal of these phenotypic alterations by antipsychotic drug further underline the pivotal role of GABRB2 in the development of schizophrenia [ 98 ]. As well, the association between GABRB2 and schizophrenia has been validated by multiple genetic studies on different ethnic populations [ 99 101 ], and SNPs, haplotypes and CNVs in the 3551-bp segment are found to be associated with schizophrenia taking a candidate gene approach [ 102 , 103 ]. However, genome-wide association studies report no significant association between any of the SNPs in this 3551-bp segment and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The overlaps of genes of nicotine addiction, glutamatergic synapses, olfactory transduction, alcoholism, systemic lupus erythematosus, hypogonadism, premature ovarian failure, and breast cancer with PMDD might be suggestive of hitherto hidden aspects of central nervous system or endocrine system involvements with PMDD. The GRIA4 gene, overlapping with the 100-kb CNV features for the C>D and V>D comparisons, groups, has also been found to be associated with schizophrenia (38), in accordance with the shared CNVs between schizophrenia and PMDD (14).…”
Section: Discussionmentioning
confidence: 60%
“…Deletion of gabrb2 genes from knockout mice also brought about schizophrenic symptoms that were alleviated by the antipsychotic Risperidone (13). Recently, analysis of germline copy-number-variations (CNVs) at the nsv1177513 site in Exon 11, and the esv2730987 site in Intron 6, of GABRB2 in PMDD and schizophrenia patients showed that CNV alterations at both esv2730987 and nsv1177513 were significantly associated with schizophrenia in Chinese and Germans as well as PMDD in Chinese (14). Moreover, subjects with different levels of susceptibility to cancer could be distinguished by means of diagnostic CNV marker features selected from the germline genomes with the application of machine learning (15).…”
Section: Introductionmentioning
confidence: 99%
“…and SNPs, haplotypes and CNVs in the 3,551-bp segment are found to be associated with schizophrenia taking a candidate gene approach [92,93]. However, genome-wide association studies report no significant association between any of the SNPs in this 3,551-bp segment and schizophrenia.…”
Section: Positive Effects Of Hotspots and Clustersmentioning
confidence: 99%